Tourmaline lyocell blend fiber and preparation method thereof
By uniformly dispersing tourmaline powder in lyocell fibers through wet ultrafine grinding and embedding it in polyvinyl alcohol microspheres, the method enhances the health care and textile properties of far-infrared fabrics.
Patent Information
- Application Number
- CN202411269156.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
Tourmaline powder agglomerates easily and is difficult to disperse uniformly in fiber fabrics, reducing the health care functions of far-infrared fabrics.
A method involving wet ultrafine grinding and air flow crushing of tourmaline powder with specific dispersants and grinding balls, followed by embedding it in polyvinyl alcohol microspheres, to achieve uniform dispersion in lyocell fibers.
The method produces tourmaline lyocell blended fibers with enhanced health care functions, such as far-infrared radiation and negative ion release, while maintaining excellent textile properties like softness and moisture absorption.
Smart Images

Figure BDA0005038159060000041 
Figure BDA0005038159060000051 
Figure BDA0005038159060000061
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of textile materials, and more specifically, to a tourmaline lyocell blended fiber and a preparation method thereof. Background Art
[0002] Far-infrared fabric is a functional fiber fabric made by adding far-infrared absorbers that can absorb far-infrared rays of different wavelengths and then radiate far-infrared rays during the processing or post-processing process. The far-infrared radiation of far-infrared fiber not only has the effect of heat preservation, but also has the effect of promoting blood circulation. It is a new type of chemical fiber raw material with both heat preservation and health care functions.
[0003] Tourmaline, also known as tourmaline, is a natural mineral with unique health functions. Its current value is equivalent to the human body's bioelectric current. In addition, it can radiate far-infrared radiation, release negative ions, and contain trace elements, so it plays an important role in human health. Therefore, tourmaline is often added to the fibers of fabrics as a raw material for making far-infrared fabrics.
[0004] At present, during the fiber processing or post-processing process, tourmaline is usually added in the form of powder. However, tourmaline powder has a high specific surface energy, is easy to agglomerate, and is not easy to disperse in the fiber, thus reducing the health care function of far-infrared fabrics. Summary of the invention
[0005] In order to improve the dispersion performance of tourmaline in fibers, the present application provides a tourmaline-lyocell blended fiber and a preparation method thereof.
[0006] In a first aspect, the present application provides a method for preparing tourmaline lyocell blended fibers, using the following technical solution: A method for preparing tourmaline lyocell blended fiber comprises the following preparation steps: S1 Tourmaline pretreatment: After mixing tourmaline powder, sodium polyacrylate, sodium hexametaphosphate and water, wet ultrafine grinding, drying, and air flow crushing are performed to obtain pretreated tourmaline powder; The diameter of the grinding balls in the wet ultrafine grinding is Φ0.8-2.0mm; The weight ratio of the tourmaline powder, sodium polyacrylate, sodium hexametaphosphate, grinding balls and water is 1:(0.005-0.025):(0.005-0.025):(1-3):(5-15); S2 Preparation of tourmaline slurry: mixing the pretreated tourmaline powder, dispersant and water to obtain tourmaline slurry; Preparation of S3 tourmaline lyocell blended fiber: Add tourmaline slurry into lyocell spinning stock solution for wet spinning to obtain tourmaline lyocell blended fiber.
[0007] By adopting the above technical scheme, sodium polyacrylate and sodium hexametaphosphate are selected as mixed dispersants, and the weight ratio of tourmaline powder, sodium polyacrylate, sodium hexametaphosphate, grinding balls and water is controlled, so that the agglomeration of tourmaline powder particles can be reduced, so that the tourmaline powder is evenly dispersed in the aqueous solution of grinding balls, etc., and then the grinding balls with a diameter of Φ0.8-2.0mm can fully grind and disperse the tourmaline powder. After air flow crushing, pre-treated tourmaline powder with most particles having a uniform and stable particle size of 0.3μm can be obtained.
[0008] By pre-mixing the pre-treated tourmaline powder, dispersant and water into a tourmaline slurry, the pre-treated tourmaline powder is dispersed in water first, which is beneficial to improving the dispersibility of the tourmaline slurry in the lyocell spinning solution. At the same time, since most of the pre-treated tourmaline powder has a uniform and stable particle size of 0.3μm, the tourmaline powder has good dispersibility, so that the tourmaline powder can be evenly dispersed in the lyocell spinning solution. Therefore, the fiber produced not only has the health care functions of tourmaline, such as promoting blood circulation and enhancing human immunity, but also retains the excellent textile properties of lyocell fiber, such as softness, smoothness, moisture absorption and perspiration.
[0009] Preferably, the grinding ball gradation is Φ2.0mm:Φ1.2mm:Φ0.8mm=1:(0.9-1.1):(0.65-0.85).
[0010] By adopting the above technical solution and selecting grinding balls with specific gradation to grind the tourmaline powder, the aggregation between the tourmaline powder particles can be effectively reduced, which is beneficial to improving the grinding efficiency of the tourmaline powder by the grinding balls.
[0011] Preferably, the air pressure of the air flow milling is 0.4-0.8 MPa.
[0012] By adopting the above technical solution, the tourmaline powder is wet ultrafine ground and then air flow crushed under the above air pressure, with high crushing efficiency. Most of the particle sizes of the obtained pretreated tourmaline powder are stable at 0.3μm, and it has a good dispersion effect in the lyocell spinning solution.
[0013] Preferably, the pretreated tourmaline powder is polyvinyl alcohol-embedded tourmaline microspheres, the wall material of the polyvinyl alcohol-embedded tourmaline microspheres is polyvinyl alcohol, and the core material includes the pretreated tourmaline powder.
[0014] Polyvinyl alcohol is a white, stable, non-toxic water-soluble polymer with biocompatibility and spinnability, and its aqueous solution has good bonding force to hydrophilic cellulose. By adopting the above technical scheme, polyvinyl alcohol-embedded tourmaline microspheres prepared by using water-soluble polyvinyl alcohol as wall material have good hydrophilicity and can form a uniformly dispersed tourmaline slurry in water. Then, the tourmaline slurry is added to the spinning solution of lyocell fiber for wet spinning, and the tourmaline slurry can be uniformly dispersed in the lyocell fiber spinning solution to improve the health care effect of the blended fiber.
[0015] Preferably, the method for preparing polyvinyl alcohol-embedded tourmaline microspheres comprises the following steps: A1: Pretreated tourmaline powder, emulsifier and oil are stirred and mixed to obtain an oil phase; A2: adding polyvinyl alcohol aqueous solution to the oil phase, stirring and mixing, adding sodium trimetaphosphate and stirring and mixing, and then adding sodium hydroxide and stirring and reacting to obtain a reactant; A3: Add anhydrous ethanol to the reactants, centrifuge, collect the precipitate, wash, and dry to obtain polyvinyl alcohol-embedded tourmaline microspheres.
[0016] By adopting the above technical scheme, under the action of an emulsifier, the pretreated tourmaline powder is first mixed with oil to form a continuous oil phase. Then, the polyvinyl alcohol aqueous solution is added to the oil phase by the method of reverse suspension-chemical crosslinking. After sufficient mixing, the polyvinyl alcohol and sodium trimetaphosphate are chemically crosslinked in an alkaline environment; finally, after post-treatment, polyvinyl alcohol-embedded tourmaline microspheres can be obtained. The preparation method of polyvinyl alcohol-embedded tourmaline microspheres of the present application is simple and suitable for large-scale production.
[0017] Preferably, the oil comprises tea tree oil and / or citronella oil.
[0018] By adopting the above technical solution, tea tree oil and / or citronella oil have good antibacterial properties, and embedding them in polyvinyl alcohol microspheres can give the microspheres antibacterial properties. When polyvinyl alcohol-embedded tourmaline microspheres absorb water and swell, the pores on the surface of the microspheres will increase, so that they are released and penetrate into the blended fibers during the wet spinning process, which is beneficial to improving the antibacterial properties of the blended fibers.
[0019] Preferably, the viscosity of the polyvinyl alcohol is 20-26.5 mPa.s, the degree of polymerization is 1650-1850, and the degree of acid hydrolysis is 86.0-90.0%.
[0020] By adopting the above technical solution, the polyvinyl alcohol-embedded tourmaline microspheres prepared by using the above polyvinyl alcohol as the wall material have a certain thermal stability, and part of the polyvinyl alcohol-embedded tourmaline microspheres can absorb water, swell and gradually dissolve during the wet spinning process, thereby exposing the embedded pre-treated tourmaline powder. Because the dissolved polyvinyl alcohol aqueous solution has good bonding properties to hydrophilic cellulose, the dissolved polyvinyl alcohol aqueous solution can bond part of the pre-treated tourmaline powder to the blended fiber, thereby improving the stability of tourmaline in the blended fiber, thereby effectively improving the health care effect of the blended fiber.
[0021] Preferably, the weight ratio of the water phase to the oil phase is 1:(5.05-5.77); The weight ratio of pretreated tourmaline powder, emulsifier and oil in the oil phase is 1:(0.16-0.25):(3.45-4.00).
[0022] By adopting the above technical solution, the pretreated tourmaline powder is mixed with excess oil to form a continuous oil phase under the action of an emulsifier. Then, the water phase and the oil phase are mixed according to the above weight ratio to prepare polyvinyl alcohol-embedded tourmaline microspheres with good coating properties.
[0023] In a second aspect, the present application provides a tourmaline lyocell blended fiber, which adopts the following technical solution: A tourmaline-lyocell blended fiber is prepared by the preparation method of the tourmaline-lyocell blended fiber.
[0024] By adopting the above technical scheme, tourmaline is pretreated and then prepared into slurry, and finally blended with lyocell fiber, so that tourmaline is evenly dispersed in the blended fiber. The obtained tourmaline lyocell blended fiber has excellent health care function, softening function and moisture absorption and perspiration function.
[0025] In summary, this application has the following beneficial effects: 1. The present application obtains pretreated tourmaline powder with a uniform and stable particle size of 0.3 μm by wet ultrafine grinding and air flow pulverization of tourmaline powder, and controls the dosage of tourmaline powder, sodium polyacrylate, grinding balls, etc. during the wet ultrafine grinding process. After blending the pretreated tourmaline powder with lyocell spinning solution, a blended fiber having both the health care function of tourmaline and the excellent textile performance of lyocell fiber is obtained. 2. The present application uses water-soluble polyvinyl alcohol as the wall material to embed the pretreated tourmaline powder, which can not only reduce the agglomeration of the pretreated tourmaline powder and improve its dispersibility in water, but also the water-soluble polyvinyl alcohol wall material absorbs water, swells and dissolves during the wet spinning process, exposing the tourmaline, so that the blended fiber has good health care function; 3. The tourmaline uniformly dispersed in the tourmaline-lyocell blended fiber of the present application can radiate far-infrared radiation, release negative ions, and has good health care functions. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to the embodiments.
[0027] Performance Testing The far infrared emissivity and elongation at break of the tourmaline lyocell blended fiber prepared in the example of the present application and the blended fiber prepared in the comparative example were tested as follows: Far infrared emissivity test: refer to GB / T 30127-2013; Elongation at break test: refer to GB / T-24218.3-2010. Example
[0028] Example 1 A tourmaline lyocell blended fiber, the components used in the preparation process and their corresponding weights (kg) are shown in the following table.
[0029] The preparation method of the above-mentioned tourmaline lyocell blended fiber comprises the following preparation steps: S1 Tourmaline pretreatment: Tourmaline powder, sodium polyacrylate, sodium hexametaphosphate and water are added to a ball mill and mixed, and then wet-milled for 45 hours, dried, and then added to a jet mill for jet milling to obtain pretreated tourmaline powder; the diameter of the grinding balls in the ball mill is Φ0.8-2.0 mm, the grinding ball grading is Φ2.0 mm:Φ1.2 mm:Φ0.8 mm=1:1:0.75, and the grinding balls are made of zirconium oxide; The air pressure in the jet mill is 0.6 MPa; Sodium polyacrylate, purchased from Shandong Xuguang Chemical Co., Ltd.; The particle size of the pretreated tourmaline powder at D90 was measured by a laser particle size distribution tester produced by Malvern Company in the UK and was 0.3 μm.
[0030] S2 Preparation of tourmaline slurry: mixing the pretreated tourmaline powder, dispersant and water to obtain tourmaline slurry; The dispersant in the embodiment of the present application is sodium hexametaphosphate.
[0031] Preparation of S3 Tourmaline Lyocell Blended Fiber: Preparation of S31 Lyocell spinning solution: A 49% by mass NMMO aqueous solution was distilled under reduced pressure to a 96% by mass NMMO aqueous solution, and then cotton pulp was added and dissolved under vacuum stirring at 125°C for 3 hours to obtain a 13% by mass Lyocell spinning solution; Spinning of S32 lyocell blended fiber: Add tourmaline slurry into lyocell spinning stock solution, stir and mix at 600r / min for 3h to obtain tourmaline lyocell spinning stock solution; The tourmaline lyocell spinning solution is added to a screw extruder, dissolved at 100°C, filtered, and then enters the spinning system, wherein the main parameters of the spinning system are controlled as follows: the air gap length is 7-9cm, the spinning speed is 35-55m / min, the spinneret aperture is 15-115μm, and the capillary length is 350-800μm. The ejected silk thread is vertically stretched in the air, enters the coagulation bath, coagulates and forms, and obtains the lyocell blended fiber; wherein the coagulation bath is a NMMO aqueous solution with a mass concentration of 12%, and the coagulation bath temperature is 0-14°C.
[0032] Washing of S33 lyocell blended fiber: immerse the lyocell blended fiber in hot water at 70° C. for 3 minutes with a bath ratio of 1:20 to obtain washed lyocell blended fiber.
[0033] Oiling of S34 lyocell blended fiber: The washed lyocell blended fiber is immersed in a 3g / L oil bath solution at an oil bath temperature of 80-85°C for 3 minutes with a bath ratio of 1:15 to obtain the oiled lyocell blended fiber.
[0034] Drying of S35 lyocell blended fiber: The oiled lyocell blended fiber is dried to obtain tourmaline lyocell blended fiber.
[0035] Example 2 A tourmaline lyocell blended fiber, which is different from Example 1 in that the components used in the preparation process and their corresponding weights (kg) are shown in the following table.
[0036] The preparation method of the above-mentioned tourmaline lyocell blended fiber comprises the following preparation steps: S1 Tourmaline pretreatment: same as in Example 1, to obtain pretreated tourmaline powder; The diameter of the grinding balls in the ball mill is Φ0.8-2.0mm, the grinding ball gradation is Φ2.0mm:Φ1.2mm:Φ0.8mm=1:0.9:0.85, and the grinding balls are made of zirconium oxide; The air pressure in the jet mill was 0.4 MPa.
[0037] The particle size of the pretreated tourmaline powder at D90 was measured by a laser particle size distribution tester produced by Malvern Company in the UK and was 0.29 μm.
[0038] S2 Preparation of tourmaline slurry: same as in Example 1, to obtain tourmaline slurry; Preparation of S3 Tourmaline Lyocell Blended Fiber: S31 Preparation of lyocell spinning solution: the same as in Example 1, obtaining a lyocell spinning solution with a mass fraction of 13%; S32 Spinning of lyocell blended fibers: the same as in Example 1, obtaining lyocell blended fibers.
[0039] Washing of S33 lyocell blended fiber: The same as in Example 1, to obtain washed lyocell blended fiber.
[0040] Oiling of S34 lyocell blended fiber: Same as Example 1, to obtain oiled lyocell blended fiber.
[0041] Drying of S35 lyocell blended fiber: Same as Example 1, to obtain tourmaline lyocell blended fiber.
[0042] Example 3 A tourmaline lyocell blended fiber, which is different from Example 1 in that the components used in the preparation process and their corresponding weights (kg) are shown in the following table.
[0043] The preparation method of the above-mentioned tourmaline lyocell blended fiber comprises the following preparation steps: S1 Tourmaline pretreatment: same as in Example 1, to obtain pretreated tourmaline powder; The diameter of the grinding balls in the ball mill is Φ0.8-2.0mm, the grinding ball gradation is Φ2.0mm:Φ1.2mm:Φ0.8mm=1:1.1:0.65, and the grinding balls are made of zirconium oxide; The air pressure in the jet mill was 0.8 MPa.
[0044] The particle size of the pretreated tourmaline powder at D90 was measured by a laser particle size distribution tester produced by Malvern Company in the UK and was 0.32 μm.
[0045] S2 Preparation of tourmaline slurry: same as in Example 1, to obtain tourmaline slurry; Preparation of S3 Tourmaline Lyocell Blended Fiber: S31 Preparation of lyocell spinning solution: the same as in Example 1, obtaining a lyocell spinning solution with a mass fraction of 13%; S32 Spinning of lyocell blended fibers: the same as in Example 1, obtaining lyocell blended fibers.
[0046] Washing of S33 lyocell blended fiber: The same as in Example 1, to obtain washed lyocell blended fiber.
[0047] Oiling of S34 lyocell blended fiber: Same as Example 1, to obtain oiled lyocell blended fiber.
[0048] Drying of S35 lyocell blended fiber: Same as Example 1, to obtain tourmaline lyocell blended fiber.
[0049] The far infrared emissivity and elongation at break of the tourmaline lyocell blended fibers prepared in Examples 1-3 were tested. The test results are shown in the following table.
[0050] By analyzing the data in the above table, it can be seen that the far-infrared emissivity of the tourmaline lyocell blended fibers prepared in Examples 1-3 is as high as 81-85%, and the dry elongation at break is as high as 16.3-16.8%. This shows that in the preparation method of the tourmaline lyocell blended fibers of the present application, a specific weight of tourmaline powder, sodium polyacrylate, sodium hexametaphosphate, grinding balls and water are first selected for wet ultrafine grinding, and then air flow pulverization is performed within a certain pressure range. The pretreated tourmaline powder obtained has a particle size uniformly and stably at 0.3 μm, is not easy to agglomerate, and has good dispersibility. Therefore, the tourmaline lyocell blended fibers prepared by using the same have good health care functions and flexibility.
[0051] Example 4 A tourmaline-lyocell blended fiber, which is different from Example 1 in that an equal weight of polyvinyl alcohol is used to embed tourmaline microspheres instead of pretreated tourmaline powder.
[0052] The polyvinyl alcohol-embedded tourmaline microspheres have a wall material of polyvinyl alcohol and a core material comprising pre-treated tourmaline powder. The raw materials used in the preparation process and their corresponding weights (g) are shown in the following table.
[0053] The method for preparing the polyvinyl alcohol-embedded tourmaline microspheres comprises the following steps: A1: Add the pretreated tourmaline powder and emulsifier into the oil, stir and mix at 50°C for 30 minutes to obtain an oil phase; Adding polyvinyl alcohol into water and stirring to mix, thereby obtaining a polyvinyl alcohol aqueous solution; In the embodiment of the present application, the pretreated tourmaline powder is the pretreated tourmaline powder prepared in step S1 of Example 1; the emulsifier is octadecyl dimethyl amine oxide; the oil is citronella oil; the viscosity of polyvinyl alcohol is 20-26.5 mpa.s, the degree of polymerization is 1650-1850, the degree of acid hydrolysis is 86.0-90.0%, and the molecular weight is 72600-81400.
[0054] A2: Add the polyvinyl alcohol aqueous solution to the oil phase, stir and mix for 30 minutes, add sodium trimetaphosphate and stir and mix for 20 minutes, then add sodium hydroxide, stir and react at 50° C. for 16 hours to obtain a reactant; A3: The reactants were allowed to stand for 30 minutes, and then a small amount of anhydrous ethanol was added, centrifuged, the supernatant was taken out, the precipitate was collected, washed with anhydrous ethanol and water three times in sequence, and dried to obtain polyvinyl alcohol-embedded tourmaline microspheres.
[0055] Embodiment 5-6 A tourmaline-lyocell blended fiber is different from Example 4 in that, during the preparation of polyvinyl alcohol-embedded tourmaline microspheres, the raw materials used and their corresponding weights (g) are shown in the following table.
[0056] Example 7 A tourmaline-lyocell blended fiber is different from Example 1 in that in the preparation process of polyvinyl alcohol-embedded tourmaline microspheres, the polyvinyl alcohol used has a viscosity of 44-50 mpa.s, a degree of polymerization of 2400-2500, a degree of acid hydrolysis of 86.0-90.0%, and a molecular weight of 118000-124000.
[0057] The far infrared emissivity and elongation at break of the tourmaline lyocell blended fibers prepared in Examples 4-7 were tested. The test results are shown in the following table.
[0058] By analyzing the data in the above table, it can be seen that the far-infrared emissivity of the tourmaline lyocell blended fibers prepared in Examples 4-6 is as high as 87-90%, and the dry elongation at break is as high as 17.1-17.6%. Compared with Example 1, the tourmaline lyocell blended fibers prepared in Examples 4-6 have higher far-infrared emissivity and dry elongation at break. This shows that in the preparation method of the tourmaline lyocell blended fibers of the present application, the pre-treated tourmaline powder is embedded in the lyocell spinning solution by using hydrophilic polyvinyl alcohol as the wall material, which can improve the dispersibility and stability of the pre-treated tourmaline powder in the lyocell spinning solution during wet spinning, thereby improving the health care function and flexibility of the tourmaline lyocell blended fibers.
[0059] At the same time, compared with Examples 1, 4-6, the far infrared emissivity and dry elongation of Example 7 are reduced. The reason may be that polyvinyl alcohol has high viscosity, high degree of polymerization and molecular weight, and is not easy to dissolve, which makes the pretreated tourmaline powder poorly dispersible and easily blocks the radiation of the pretreated tourmaline powder, thereby reducing the health function and flexibility of the tourmaline lyocell blended fiber.
[0060] Comparative Example Comparative Example 1 A blended fiber, which is different from Example 1 in that an equal weight of polypropylene hydrochloric acid is used to replace sodium polyacrylate; and the diameter of the grinding ball is Φ3.0-5.0 mm.
[0061] Comparative Example 2 A blended fiber, which is different from Example 1 in that an equal weight of viscose spinning solution is used to replace the lyocell spinning solution, wherein the viscose spinning solution has a methyl cellulose content of 8.8%, an alkali content of 5.2%, a viscosity of 55S, and a degree of maturity of 16H±1.5.
[0062] The method for preparing the blended fiber comprises the following steps: S1 Tourmaline pretreatment: same as Example 1, to obtain pretreated tourmaline powder.
[0063] S2 Preparation of tourmaline slurry: The same as Example 1, to obtain tourmaline slurry.
[0064] Preparation of S3 blended fiber: The tourmaline slurry and the viscose spinning stock solution were stirred and mixed for 3 hours, and then wet-spun, and then washed, oiled and dried to obtain the blended fiber.
[0065] The far infrared emissivity and elongation at break of the blended fibers prepared in Comparative Example 1-2 were tested, and the test results are shown in the following table.
[0066] Compared with the blended fiber of comparative example 1, the far infrared emissivity of the tourmaline lyocell blended fiber of example 1 is relatively increased by 8.97%, and the dry elongation at break is relatively increased by 5%. This shows that in the preparation method of the tourmaline lyocell blended fiber of the present application, sodium polyacrylate and sodium hexametaphosphate are used as composite dispersants to improve the dispersibility of the tourmaline powder, so that it can be fully wet-milled to obtain the pretreated tourmaline powder, which can be evenly dispersed in the lyocell spinning solution, thereby obtaining the tourmaline lyocell blended fiber with both health care function and flexibility.
[0067] Compared with the blended fiber of comparative example 1, the far infrared emissivity of the tourmaline lyocell blended fiber of example 1 is relatively increased by 11.84%. This shows that in the total raw materials for preparing the tourmaline lyocell blended fiber of the present application, the tourmaline lyocell blended fiber is blended with tourmaline and lyocell spinning solution, and the obtained tourmaline lyocell blended fiber has a higher health function.
[0068] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing tourmaline lyocell blended fiber, characterized in that: The method comprises the following preparation steps: S1 Tourmaline pretreatment: After mixing tourmaline powder, sodium polyacrylate, sodium hexametaphosphate and water, wet ultrafine grinding, drying, and air flow crushing are performed to obtain pretreated tourmaline powder; The diameter of the grinding balls in the wet ultrafine grinding is Φ0.8-2.0mm; The weight ratio of the tourmaline powder, sodium polyacrylate, sodium hexametaphosphate, grinding balls and water is 1:(0.005-0.025):(0.005-0.025):(1-3):(5-15); S2 Preparation of tourmaline slurry: mixing the pretreated tourmaline powder, dispersant and water to obtain tourmaline slurry; Preparation of S3 tourmaline lyocell blended fiber: Add tourmaline slurry into lyocell spinning stock solution for wet spinning to obtain tourmaline lyocell blended fiber.
2. The method for preparing the tourmaline lyocell blended fiber according to claim 1, characterized in that: The grinding ball gradation is Φ2.0mm:Φ1.2mm:Φ0.8mm=1:(0.9-1.1):(0.65-0.85).
3. The method for preparing the tourmaline lyocell blended fiber according to claim 1, characterized in that: The air pressure of the air flow milling is 0.4-0.8 MPa.
4. The method for preparing the tourmaline lyocell blended fiber according to claim 1, characterized in that: The pretreated tourmaline powder is polyvinyl alcohol-embedded tourmaline microspheres, the wall material of the polyvinyl alcohol-embedded tourmaline microspheres is polyvinyl alcohol, and the core material includes the pretreated tourmaline powder.
5. The method for preparing the tourmaline lyocell blended fiber according to claim 4, characterized in that: The method for preparing polyvinyl alcohol-embedded tourmaline microspheres comprises the following steps: A1: Pretreated tourmaline powder, emulsifier and oil are stirred and mixed to obtain an oil phase; A2: adding polyvinyl alcohol aqueous solution to the oil phase, stirring and mixing, adding sodium trimetaphosphate and stirring and mixing, and then adding sodium hydroxide and stirring and reacting to obtain a reactant; A3: Add anhydrous ethanol to the reactants, centrifuge, collect the precipitate, wash, and dry to obtain polyvinyl alcohol-embedded tourmaline microspheres.
6. The method for preparing the tourmaline lyocell blended fiber according to claim 4, characterized in that: The oils include tea tree oil and / or citronella oil.
7. The method for preparing the tourmaline lyocell blended fiber according to claim 4, characterized in that: The viscosity of the polyvinyl alcohol is 20-26.5 mPa.s, the degree of polymerization is 1650-1850, and the degree of acid hydrolysis is 86.0-90.0%.
8. The method for preparing tourmaline lyocell blended fiber according to claim 1, characterized in that: The weight ratio of the water phase to the oil phase is 1:(5.05-5.77); The weight ratio of pretreated tourmaline powder, emulsifier and oil in the oil phase is 1:(0.16-0.25):(3.45-4.00).
9. A tourmaline lyocell blended fiber, characterized in that: The fiber is prepared by the preparation method of the tourmaline lyocell blended fiber according to any one of claims 1 to 8.
